DETERMINATION AND EVALUATION OF TRICHOPHYTIC DISEASE IN PEDIGREE CATTLE BY SEASONS - Usmonova Xadicha Jo’rayevna (Web of Journals Publishing, 2025)
This article addresses the identification and epidemiological assessment of trichophytosis among pedigree cattle across different seasons of the year. The study was conducted in several regions of Uzbekistan. Analysis results indicated that the highest incidence of the disease occurred in late winter and early spring. Seasonal changes, air humidity, and zoohygienic conditions significantly influence the spread of trichophytosis. Based on the research findings, recommendations were made for early diagnosis of the disease and the enhancement of preventive measures depending on the season.
Keywords: Trichophytosy, pedigree cattle, seasonality, dermatophytosis, epidemiology, Uzbekistan, disease prevalence.